Developing a set of criteria for defining the roles and responsibilities of the different types of heart failure disease management programs in Ontario: A mixed methods study - Hinton, Stephanie Nicole (University of Waterloo, 2015)
As part of the provincial strategy for heart failure (HF) management proposed by the Cardiac Care Network (CCN), an environmental scan survey was conducted to determine the current state of heart failure management in Ontario. Results of the scan suggested wide variation in the operation of outpatient HF disease management programs in Ontario. The overall research aim of this study was to develop a set of criteria for defining the roles and responsibilities of the different types of outpatient HF disease management programs in Ontario and to create a list of recommendations to assist with the optimization of the quality and role of these different types of outpatient HF disease management programs. The study used a mixed methods design that combined quantitative and qualitative methods. The quantitative component used secondary data analysis to classify outpatient heart failure disease management programs and the qualitative component used input from focus groups to develop a finalized set of criteria and identify barriers and facilitators to adopting the criteria. The quantitative and qualitative data were also methodologically triangulated to develop the list of recommendation. Four outpatient HF disease management programs and 17 care providers participated in the study. The quantitative component found that there was agreement regarding the classification of all four outpatient HF disease management programs. The qualitative component finalized a set of criteria that included six domains: patient population, frequency of follow-up appointments, complexity of the HF program, timely access to care, type of delivery personnel, and environment; and identified nine barriers and four facilitators to adopting it. The set of criteria incorporate a checklist under each domain to serve as a guideline for describing the roles and responsibilities that are specific to each type of outpatient HF disease management program. Additionally, four recommendations were developed from the data triangulation process. The development of a standardized set of criteria for defining the roles and responsibilities of heart failure disease management programs and the associated recommendations are important steps towards implementing a HF management strategy in Ontario. This approach will help to optimize outpatient HF management and improve health outcomes for HF patients.
Keywords: Heart Failure; Disease Management Programs; Health Studies and Gerontology